AN ANALYSIS OF USING WEBTOON IN IMPROVING STUDENTS’ READING MOTIVATION AT FIRST SEMESTER - Desi Minawati; Deri Sis Nanda; Mery Damayanti Sihotang; Christofora Desi Kusmindari (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2021)
The purpose of this study was to analyze the use of Webtoon to improve students' reading motivation in the first semester of the English department, Bandar Lampung University. The population used in this study was 15 Students. This research used purposive sampling technique. Data was collected using observations, questionnaires and interviews. Interviews were used to find out more about using the Webtoon that is used. The technique used in this study was purposive sampling. The results of the study show that most students were motivated to read when using a Webtoon, it was caused reading using the media, would influence students' desire to do something. This research could have implications for English language teachers, students, and further researchers.